Penerapan Mobilisasi Miring Kanan-Miring Kiri untuk Pencegahan Dekubitus pada Pasien Stroke - Latifatul Nur Aliyyah; Fida’ Husain (NAJ Nursing Applied Journal, 2024)
Background: Impaired mobility in stroke patients often causes excessive pressure on the skin, increasing the risk of pressure ulcers. If left untreated, decubitus wounds can get worse and lead to infection. Based on evidence, regular right-left tilt mobilization is a potential intervention to prevent pressure ulcers. Objective: Analyze the application of right-slant-left-slant mobilization to prevent pressure ulcers in stroke patients at Ibu Fatmawati Soekarno Regional Hospital, Surakarta City. Method: Descriptive research design with a case study approach, carried out every 3 hours on 2 respondents to explore the application of right oblique-left oblique mobilization in preventing pressure ulcers in stroke patients. Results: Before implementing the right oblique-left oblique mobilization every 3 hours the respondent was at moderate risk with a score of Tn .S 15, Ny.S 16 and pressure ulcers can be prevented. Conclusion: There is an effect of tilting mobilization to the right and left which is indicated by a decrease in the risk of developing pressure ulcers at the Ibu Fatmawati Soekarno Regional Hospital, Surakarta City.